ANALISIS ALOKASI DANA DESA DALAM PEMBANGUNAN EKONOMI PERSPEKTIF IBNU KHALDUN - Munawar, Rizal; Nursyafika, Nursyafika; Lasmi, Lasmi; Nurhalifah, Nurhalifah; Naimah, Naimah; Ameliah, Nur Cahya (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This research aims to reveal how the village fund budget (ADD) is allocated in the economic development process from Ibn Khaldun's perspective. with special emphasis on how this concept can be applied at the village level, especially in Bima district. In his work